Effect of magnetic therapy on selected physical performances - Schall, D. M.; Ishee, J. H.; Titlow, L. W. (The Journal of Strength and Conditioning Research, 2003)
The purpose of this study was to investigate the effects of magnetic therapy in the form of shoe insoles on vertical jump, bench squat, 40-yd dash, and a soccer-specific fitness test performance. Subjects were 14 collegiate male soccer players who were pretested, retested 3 weeks later, and then placed into a double-blind control or treatment group using a matching procedure. The control group received magnetic shoe insoles with a rating of 125 gauss, and the treatment group received insoles with a rating of 600 gauss. Subjects wore the insoles during practice and games for 7 weeks and were then retested. Results indicated significant differences among test scores during the 3 time periods but not between the treatment and control groups. There was a decline in 40-yd dash performance from the initial evaluation (5.10 seconds) to the final evaluation (5.08 seconds). There were no other significant differences. Within the limitations of the study, magnetic therapy did not improve physical performance.